Human papilloma virus genotypes in dysplasia and epithelial hyperplasia of oral cavity using the luminex xmap technology. A multicenter study (2020)
Background: Oral cancer associated with high risk (HPV-HR) human papilloma virus (HPV) has been increasing. HPV-HR has been associated with epithelial dysplasia, however, little information exists on its frequency in epithelial hyperplasia lesions. The aim of this study is to compare HPV genotypes in dysplastic and hyperplastic lesions of oral cavity. Material and Methods: Two hundred and fifty oral lesions: 131 dysplasia and 119 hyperplasia from two regions of Colombia were evaluated. One hundred seventy-four coming from urban area and 104 from a high risk population to oral cancer from a rural area. HPV was identified by qPCR and Twenty-four HPVs genotypes were evaluated by Luminex® technology. Logistic regressions were performed to establish the associations between HPV infections with oral dysplasia. Results: Twenty-eight percent (70/250) of the samples were positives for any HPV and HPV-HRs were more frequently than low risk HPVs. HPV-16 was the most detected genotype (16%) followed by HPV-31, 53, 18 and 45. HPV, HPV-HRs and HPV-16 were only associated with dysplasia in urban area; OR 3.28 (CI 95% 1.49-7.17), OR 7.94 (CI 95% 2.97-21.2) and OR 5.90 (CI 95% 2.05-17). Individuals in rural area showed more HPV and HPV-HRs infection in hyperplasic lesions than urban population. The majority of HPV+ lesions had multi-type of HPV (52/70) and the urban individuals showed more genotypes than rural population. Conclusions: HPV-.HRs are frequently found in hyperplastic and dysplastic epithelial lesions. HPV-HRs and HPV-16 were associated with dysplasia in urban population. Rural high risk population and urban population differ in the frequency and variety of HPV genotypes.